La place de l'eucalyptus à Addis-Abeba - Delphine Ayerbe (Territoire en Mouvement)
Addis Ababa is moved by urban transformations that give a new face to the Ethiopian capital. Infrastructures are modified. Individual housings are globally changed into collectives accommodations and buildings appear, revealing authorities’ willings to reshape Addis Ababa into a modern city. Those changes go with the hope to enhance the city on international scene. For this, urban environment is highlighted. Green spaces, especially eucalyptus-forested highlands, are concerned by new urban projects. On the one hand, eucalyptus trees are rejected, but on the other hand, urban forest is promoted as a part of green city. Fieldwork based on interviews with stakeholders, on the study of urban projects – institutional papers, speechs, press - reveal this paradox. By using urban environmental approach, the paper attempts to shed light on the ambiguous gap between the projected city and the lived city in this changing capital. We thus emphasise that politic authorities want to show that they have integrated global discourses on sustainable development in order to promote Addis Ababa as a world city. This mechanism is based on a subtle use of the existing.